Performance of Front Office Employees at the Bintang Sintuk Bontang Hotel - Fitriyani, Endah; Evita, Anastasia (Journal of Tourism Education, 2021)
Employee performance is very important for a company to realize the company's goals. Without good performance, it is difficult for a company to achieve optimal results. Optimizing human resources is the main focus of the organization in improving performance. So it can be said that human resources are a key factor in obtaining good performance. Front Office employees must carry out their roles and functions properly because otherwise the operations of other departments will be disrupted. Front Office employees must always maintain their good performance. However, in practice, there are still many obstacles experienced by Front Office employees, one of which is the performance factor in discipline, communication, and accuracy at work. So to analyze these problems, the authors made direct observations, designed and made a list of questions related to research, and disseminated them to Front Office employees at the Sintuk Bintang Hotel. Furthermore, the authors conducted interviews with the Front Office Manager and also Personnel and conducted a literature study to find and use the theoretical foundations related to the problem under study. The result of this research is that discipline gets a bad score, while communication and discipline are still in the category of adequate assessment. From these results, it is hoped that the hotel management will be open to suggestions given by employees so that communication can develop and run well and conduct regular training to get good Front Office employee performance.